Necessity and Reconstruction Methods of Splenic Vein After Resection of the Portomesenteric Junction During Resections for Pancreatic Cancer - Moath Alarabiyat; Nikolaos Chatzizacharias (Current Oncology, 2025)
Pancreatic cancer involving the porto-mesenteric junction (PMJ) represents a challenge to pancreatic surgeons. Restoring mesenteric venous drainage is an essential component of vascular reconstruction after tumour resection. In contrast, management of the splenic venous drainage can involve the ligation or reconstruction of the splenic vein (SV). Evidence suggests that splenic vein ligation (SVL) is commonly associated with sinistral portal hypertension (SPH), especially if multiple venous tributaries were divided to facilitate resection. Although the association between SVL and SPH is well documented, the risk of symptomatic SPH is not widely reported, presumably due to the low incidence and poor survival of pancreatic cancer patients. Splenic vein reconstruction (SVR) has been proposed to decrease the risk of SPH but is fraught with technical complexity and increased morbidity. Moreover, SVR does not guarantee the prevention of SPH, as patency rates vary and associated hemodynamic changes are unpredictable. Patient selection and the surgical expertise available can guide SV intraoperative management, taking into consideration the risks and benefits associated with each approach. A comprehensive review of the current literature highlighting the incidence and clinical impact of SPH after the resection of pancreatic cancer involving the PMJ is presented.